MANUAL THERAPY FOR TREATING SACROILIAC JOINT PAIN DISORDERS - Frank, Sergii; Frank, Michael; Frank, George (World Science, 2020)
Pain in sacroiliac joint structures and their dysfunction constitutes a large portion of lumbosacral spine pathologies. Their symptoms are diverse as they are associated with inflammatory processes in the joints themselves, as well as the instability of the joints and their supporting ligaments. All components of these structures can be a source of pain, so it is quite difficult to diagnose and treat this disease. Treatment of sacroiliac joint pathologies needs to be multifaceted. This study proves that manual therapy combined with shock wave therapy can successfully aid patients with treatment-resistant pain syndromes and dysfunction of sacroiliac joints who haven’t been able to achieve their desired results through conventional conservative and surgical treatment.